2014
DOI: 10.1371/journal.pone.0107757
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Extract Induces a Phenotypic Shift in Epithelial Cells; Involvement of HIF1α in Mesenchymal Transition

Abstract: In COPD, matrix remodeling contributes to airflow limitation. Recent evidence suggests that next to fibroblasts, the process of epithelial-mesenchymal transition can contribute to matrix remodeling. CSE has been shown to induce EMT in lung epithelial cells, but the signaling mechanisms involved are largely unknown and subject of this study. EMT was assessed in A549 and BEAS2B cells stimulated with CSE by qPCR, Western blotting and immunofluorescence for epithelial and mesenchymal markers, as were collagen prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 43 publications
3
32
3
1
Order By: Relevance
“…We have shown that hypoxia signaling is involved in the induction of a phenotypic shift of epithelial cells by cigarette smoke extract, especially with respect to the mesenchymal transition (8). In the current study, in the context of TNF-a-induced EMT, no role for hypoxia signaling could be demonstrated.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We have shown that hypoxia signaling is involved in the induction of a phenotypic shift of epithelial cells by cigarette smoke extract, especially with respect to the mesenchymal transition (8). In the current study, in the context of TNF-a-induced EMT, no role for hypoxia signaling could be demonstrated.…”
Section: Discussioncontrasting
confidence: 64%
“…We have shown a role for c-Jun N-terminal kinase (JNK) 1 in TGF-b1-induced EMT in lung epithelial cells, as the induction of this phenotypic shift was blunted in JNK1 knockout cells (7). Furthermore, our group recently demonstrated that cigarette smoke extract also has the ability to induce such a phenotypic shift, in which hypoxia inducible factor (HIF1a) signaling was implicated (8).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Although the pathogenesis of ERM has not yet been fully elucidated, the formation and progression of ERM can be regarded as a fibrotic process because the pathologic findings include increased ECM protein deposition and membrane contraction in which myofibroblasts play a crucial role1. Several studies have demonstrated that exposure to cigarette smoke extracts can provoke activation of the TGF β pathway and the epithelial-mesenchymal transition (EMT)4445, and thereby up-regulate numerous genes involved in fibrosis and the accumulate of ECM28 and these processes are also known to plays a crucial roles in the pathogenesis of ERM. However, the results of epidemiologic studies of the relationship between smoking and risk of ERM have remained inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Beas-2B cells were cultured in BEBM media (Lonza Inc., Allandale, NJ, USA) supplemented with a BEGM kit (Lonza Inc.) without the gentamycin-amphotericin B mix. Cigarette smoke extract (CSE) was made essentially by the method detailed in Eurlings et al [30]. Filters were removed from 3R4F Research cigarettes (University of Kentucky, Lexington, KY) and CSE was made by bubbling the smoke of one cigarette into 10 mls of full media using a linear pump (2 mL/sec).…”
Section: Methodsmentioning
confidence: 99%